Treatment Of Domestic Liquid Waste Using Filtration And Adsorption Methods At Villa Citra Makale Housing - Reni Oktaviani Tarru; Harni Eirene Tarru; Wiwinda Ekalisa; Febi Trisa Wahyuni (Eduvest - Journal of Universal Studies, 2021)
Domestic liquid waste comes from household activities that contain pollutants that can contaminate soil and water bodies. If the waste is simply dumped into a water body without being treated first, it can pollute the surrounding environment, so the aim of the study was to determine the volume of wastewater produced and to treat the waste using filtration and adsorption methods. The research method used is descriptive quantitative method by calculating the amount of water use to get the volume of wastewater and wastewater treatment with filtration and adsorption methods. The results showed that the volume of wastewater produced was 11.14 m3/day, and the results of wastewater treatment with filtration and adsorption methods showed that several parameters had decreased, namely the BOD value of 27.38%, Total Coliform of 93.95%, and color of 75%.